2003
DOI: 10.1021/ac034876a
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor-Based Determination of Riboflavin in Milk Samples

Abstract: An assay for quantification of riboflavin (Rf) in milk-based products has been developed using the principle of surface plasmon resonance with on-chip measurement. The quantification was done indirectly by measuring excess of Rf binding protein (RBP) that remains free after complexation with Rf molecules originally present in the sample solution. The chip was modified with covalently immobilized Rf in order to bind the RBP in excess. A chemical modification was performed to introduce a reactive ester group at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 30 publications
(39 reference statements)
2
34
0
Order By: Relevance
“…5B gave the enlarged linear part, and the linear calibration equations and their corresponding parameters for the three electrodes were listed in Table 1. It was found that the correlation coefficients for all calibration models were them, the limit of detection given by the rMoS 2 -graphene/A 32 /Au electrode was well comparable with or superior to those values obtained from other analytical methods [35][36][37]. Derived from the slope of the linear calibration models, the order of the sensitivity for the three electrodes toward riboflavin can be obtained as follows: rMoS 2 -graphene/A 32 /Au electrode (0.83 lA lM À1 ) ) bare Au electrode (0.044 lA lM À1 ) > A 32 /Au electrode (0.015 lA lM À1 ).…”
Section: Dpv Sensing Of Riboflavin At the Rmos 2 -Graphene/a 32 /Au Esupporting
confidence: 70%
See 1 more Smart Citation
“…5B gave the enlarged linear part, and the linear calibration equations and their corresponding parameters for the three electrodes were listed in Table 1. It was found that the correlation coefficients for all calibration models were them, the limit of detection given by the rMoS 2 -graphene/A 32 /Au electrode was well comparable with or superior to those values obtained from other analytical methods [35][36][37]. Derived from the slope of the linear calibration models, the order of the sensitivity for the three electrodes toward riboflavin can be obtained as follows: rMoS 2 -graphene/A 32 /Au electrode (0.83 lA lM À1 ) ) bare Au electrode (0.044 lA lM À1 ) > A 32 /Au electrode (0.015 lA lM À1 ).…”
Section: Dpv Sensing Of Riboflavin At the Rmos 2 -Graphene/a 32 /Au Esupporting
confidence: 70%
“…Hence, the sensitive and selective detection of riboflavin is of great importance. At present, various analytical methods [34][35][36][37] including high-performance liquid chromatography, surface plasmon resonance, mass spectrometry, fluorescence, and spectrophotometry, have been established for the detection of this analyte. However, most of the analytical techniques require complicated instrumentation, have relatively high cost, or suffer from poor sensitivity and low selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is important, of course, to protect samples from UV light during this preparation. The assay was assessed independently during the AOAC PTM study, being compared directly with the offi cial fl uorimetric method described above; the results are given in Table 4.4 [3,23] .…”
Section: Vitamin Bmentioning
confidence: 99%
“…Of the 678 articles that stated which Biacore platform was used, most utilized 2000 and 3000 platforms [222, (33%) and 249 (37%), respectively]. Investigators also reported data obtained from Biacore X (129, 19%) and 1000 (57, 8%), as well as from S51 [273,818,831,843,865], J [223,285,737,745,759], Q [892,905,907,910,913], Bialite [492,726,787,873] and Probe [348] platforms.…”
Section: Instrumentsmentioning
confidence: 99%